THE USE OF PRE-QUESTIONING TECHNIQUE AND INSTAGRAM TO COMPREHEND NARRATIVE READING TEXTS - Rosani , Ani; Asi, Natalina; Usadiati, Wahyuningsih (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2019)
The study was conducted to know the effect of pre-questioning technique and Instagram on reading comprehension of narrative text of legend. True experimental in randomized-groups-posttest-only control group design was applied to the tenth grade students of SMAN 3 Palangka Raya in academic year 2017/2018 chosen as the sample of the study. Reading test in form of multiplechoice was used as the main instrument in order to collect the data needed. The data obtained were analyzed statistically using Mann-Whitney U Test. The result of this study shows that the use of pre-questioning technique and Instagram gave a significant effect on reading comprehension of narrative text of the tenth grade students of SMAN 3 Palangka Raya in Academic Year 2017/2018.